ЕCONOMIC FRAMEWORK OF THE BIO-BASED PRIMARY SECTOR IN BULGARIA - N. Markov (Trakia Journal of Sciences)
The effective management of bioeconomy requires a structural and dynamic analysis of the primary sector. The aim of the present study is to gauge the size of the bio-based primary sector in Bulgaria. Results indicate that in Bulgaria the capacities of the bio-based sector are not used rationally. Conclusions are intended to define national priorities and policies in the area of bioeconomy.